Age Specific Behavioral Variability of Creek Chub Minnows after Exposure to Various Chemicals - Leiztke, Taren; Wold, Michael; Flynn, Mackenzie; Fischer, Andrew; Radeke, Leah; Lonzarich, David (My University, 2017)
Fish of the superorder Ostariophysi contain alarm substances that elicit fear responses in neighboring conspecifics. Research over the past decade has revealed a strong ontogenetic component to the nature of this response and revealed at least two candidate odorants for the alarm behavior. This project examined the change in response between young and old Creek Chub exposed to skin extract and chondroitin sulfate. To quantify movement tanks were marked with gridlines; movements were recorded before and after treatments in order to establish baseline activity. Future projects detecting activity in the olfactory bulb will indicate which neural pathways are employed during the response in young and old fish to skin extract and chondroitin sulfate.
Color poster with text graphs.
Keywords: Creek Chub (semtilus atromaculatis); Alarm odorants; Chondroitin sulfates; Posters